Economic impact of sovereign debt credit rating revision - Pour, Reza Tahmoores (2017)
Sovereign rating is a key element of how investors perceive the relative risk of investing in Treasury securities of a foreign country. Numerous scholars have studied rating change impacts on a given economy and on the financial performance of capital markets to news of rating changes. Hence, a continuing study of rating changes is worthy of further study using data from multiple countries in one study on the response of share markets using data from most recent years after the Global financial crisis. The gaps in literature are (i) lack of study on how sovereign rating changes affect (bond and) share markets of G20 countries, (ii) lack of research to examine the significance of sovereign rating changes before and after a crisis such as the recent global financial crisis. There is no theory for measuring economic sustainability of debt, so (iii) there are no studies on what factors are related to sustainability of debt taking by sovereign borrowers. The aim of this study is to fill such gaps in the sovereign rating literature by (a) adopting a new method of analysis to (b) study selected countries not yet studied and (c) find how financial markets react to sovereign rating revisions over recent years. We measure the change in market prices to each unit change in sovereign rating, and then proceed to find some key economic variables that are the drivers of the rating changes. The methods for this study are: (i) the widely used event study method to find out the significant impact on market prices from sovereign rating changes before and after the event rating change dates and (ii) using the panel regression to examine the factors affecting the sovereign rating changes after controlling the country heterogeneity using a latest econometric method. To estimate the probability of the different events, we run a probit regression for sovereign rating changes relating to some common determinants. Results of the study are interesting, and could contribute to the literature significantly. It is found that sovereign rating changes significantly affect share market prices. It seems that there is information leakage prior to sovereign rating announcement dates as released by the S&P: there are some negative price effects as well on mixed-type rating change effects, such as ‘rating watch’ announcements. Among the various economic variables, Gross National Saving has the biggest positive impact on sustainability of debt taking and on sovereign rating changes: it has the biggest probability of affecting the outcome. Debt serviceability has also the highest probability of changing sovereign rating grade by 0.096. These are new findings that may help to extend the sovereign rating literature in terms of findings from multiple countries, and on sustainability of debt taking. The methodology we have adopted promises to improve the existing use of research methods on this topic.